Analysis of New-Fangled Mandelbrot Sets Controlled by TAN Function (International Journal of Engineering and Computer Science, 2014)
In this paper we have presented the complex dynamics of new-fangled fractal controlled by transcendental function i.e. tan function using iterative procedure known as Ishikawa Method. Fractals are generated and analyzed for integer and non-integer values. New Mandelbrot sets are generated for different values of parameters defined by Ishikawa iteration i.e. s, s’ and transcendental controlled function. Here different ovoid’s or lobe are analyzed and our study relies on the generation of pattern defined by mini Mandelbrot sets.